Land Surface Temperature Calculation Using SEBAL and Decision Tree Methods Based on ETM + Image in RS, GIS Environment in the Maragheh Central Region - Saeed Jahanbakhsh; Majid Zahedi; Khalil Valizadeh Kamran (نشریه جغرافیا و برنامه‌ریزی, 2012)
In a wide variety of scientific climatology studies earth surface temperature, is important, Astronomy, meteorology hydrology, ecology, geology, medical science, design and optimization of transportation network and site selection of fire extinction and particularly cases required. In the calculation of the actual evapotranspiration also we consider these.. Considering the earth's surface temperature monitoring in a limited number of meteorological stations to the distribution point and the need to place the surface temperature in a wide area and at the same time the surface temperature were estimated. To access the earth's surface temperature and classification SEBAL algorithm and decision tree were used. Using ETM + image dated 31 August 2000 and pre- process, files became ready for implementation. For processing of SEBAL method. the above mentioned software Envi4.5 and ArcGIS9.3 were used. This paper estimates the difference less than 5.57° C, temperature difference between a satisfactory level was estimated through remote sensing and statistics. Temperature measured from ground level 12 years (1993 - 2005) in Maragheh meteorological station was achieved. Temperature was estimated through remote sensing and studies applicable in earth sciences research and the environment.